(untitled) (Journal of Global Humanities and Social Sciences, 2025)
The artistic achievement of Thomas Hardy’s novels is manifested not only in their rich Victorian cultural connotations—conveyed through masterful scene-painting and vivid characterizations—but also in his distinctive natural narrative style and the consistently poetic tone with which he meditates on lived experience and the surrounding world. In Hardy’s literary universe, nature is imbued with emotions, moods, and even intentions reminiscent of humans. Particularly noteworthy is his portrayal of animals, which leaves a lasting and profound impression. These creatures share a peculiar intimacy with the human protagonists, often engaging in a form of tacit communication that transcends the ordinary. Through this transcendental narrative strategy—projecting human emotions onto natural entities and refracting human consciousness, feelings, and personalities through animal depictions—Hardy vividly illuminates the inner psychological landscapes of his characters while simultaneously offering penetrating insights into the transformations of his era.